Injury to the diaphragm: Our experience in Union Head quarters Hospital - Radjou, Angeline Neetha (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Diaphragmatic injury is a global diagnostic and therapeutic challenge. OBJECTIVES: The study was to identify the variations in the risk factors, diagnosis, management, and outcome between blunt and penetrating injuries of the diaphragm. MATERIALS AND METHODS: A prospective study was conducted on patients who were diagnosed with injury to diaphragm during preoperative, intraoperative, or postmortem period. The risk correlates and the trail of events following injury, interventions, and outcomes were studied. RESULTS: Of the 25 cases, blunt injury was experienced by 10. Road traffic injury was the most common cause in blunt trauma and assault with knife in penetrating trauma. Acute presentation was the most common mechanism. X-rays were positive in 52% cases. The most common reason for false negative X-rays was massive effusion/hemothorax. Computed tomography (CT) improved the positivity rate to 62.5%. A total of 25% of diaphragmatic injuries were diagnosed during surgery for hemodynamic instability irrespective of initial X-rays findings. Laprotomy alone was sufficient in majority of cases. The defects were largely in the left side; mean defect size was more in blunt trauma. Associated injuries were noted in 92%. Stomach was most affected in penetrating injuries and spleen in blunt trauma. Empeyma was the most common morbidity. Mortality rate of 13% in penetrating injury was far lower than 60% in blunt injury. Mean Injury Severity Score (ISS) was significantly related to the fatal outcomes irrespective of mechanism. Diagnostic laparoscopy for asymptomatic low velocity junctional penetrating wounds revealed diaphragmatic injury in 20%. CONCLUSIONS: The incidence of multisystem injuries at our trauma center is on the rise. A high index of suspicion is needed for diagnosis of diaphragmatic injury. The need for thorough exploratory laprotomy is essential. In resource stretched setting like ours, the need for routine diagnostic laparoscopy in asymptomatic junctional wounds has to be validated further.